Design of a thermoelectric energy source for water pumping applications: A case study in Sharjah, United Arab Emirates - Waleed Obaid; Abdul-Kadir Hamid; Chaouki Ghenai; Mamdouh El Haj Assad (Institute of Advanced Engineering and Science, 2021)
There are many water pumping power systems that exist nowadays relying on conventional and renewable energy sources such as mechanical windmills, solar photovoltaic (PV) panels, wind turbines, and diesel generators. Few designs utilize thermoelectric modules for the purpose of enhancing the reliability and the performance of the system in order to provide water supply to isolated zones continuously. The use of thermoelectric (TE) modules is increasing due to their reduced prices and the possibility of using them in different applications depending on the required specifications of motors and other connected loads. This paper proposes a renewable energy system design for water pumping applications in Sharjah (Latitude 25.29°N and Longitude 55°E), United Arab Emirates. The system involves TE modules for operating the three-phase AC water pumping motor, voltage regulator, voltage boost converter, and three-phase power inverter while considering the changes of temperature values which affect the performance of the thermoelectric generator (TEG) modules. The aim is integrating TEG modules to cover the increasing demand of water in rural areas since rainy days in Sharjah are limited and the temperature is high. The performances of the proposed system will be demonstrated using Simulink simulations for the overall blocks of the proposed system.